Proteolytic degradation of dinitrogenase reductase from Anabaena variabilis (ATCC 29413) as a consequence of ATP depletion and impact of oxygen. - Durner, J (1996)
Both components of nitrogenase, dinitrogenase and dinitrogenase reductase, are rapidly inactivated by oxygen. To investigate the proteolytic degradation of dinitrogenase reductase irreversibly destroyed by high oxygen concentrations, we carried out in vitro experiments with heterocyst extracts from Anabaena variabilis ATCC 29413. The results indicate a direct dependence of degradation on the applied oxygen concentration. Although the degrees of degradation were similar for both the modified and unmodified subunits of dinitrogenase reductase, there was a significant difference with respect to the cleavage products observed. The pattern of effective protease inhibitors suggests the involvement of serine proteases with chymotrypsin- and trypsin-like specificity. A protective effect was obtained by saturation of the nucleotide binding sites of dinitrogenase reductase with either ATP or ADP. As shown by gel filtration experiments, the adenylates prevented the nitrogenase subunits from extensive noncovalent aggregation, which is usually considered evidence for a denaturing process. The in vitro degradation of dinitrogenase reductase is discussed in connection with previous reports on degradation of nitrogenase in cyanobacteria under oxygen stress and/or starvation.